PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI STRATEGI PEMBELAJARAN AKTIF TIPE FLIP CHART PADA SISWA KELAS X.IIS.3 MAN 2 PASAMAN BARAT - IBTAL IBTAL (JURNAL MANAJEMEN PENDIDIKAN, 2019)
Based on the learning outcomes of Class X.IIS.3 students MAN 2 Pasaman Barat in Indonesian subjects it was found that Indonesian Language Learning Outcomes are still low. The purpose of this study is to describe and obtain information about improving Indonesian Language Learning Outcomes through the Active Learning Strategy of Flip Chart Types in Class X.IIS.3 Students MAN 2 Pasaman Barat. This research is a classroom action research. Research procedures in this study include planning, action, observation and reflection. This research consisted of two cycles with four meetings. The research subjects consisted of 36 students of Class X.IIS.3 MAN 2 Pasaman Barat. Research data were collected using a test sheet. Data were analyzed using percentages. Based on the results of research and discussion that has been proposed, it can be concluded that the Active Learning Strategy of Flip Chart Type can improve Indonesian Language Learning Outcomes in Class X.IIS.3 Students MAN 2 Pasaman Barat. Student learning activities in the first cycle was 69.67 increased to 84.36.